(untitled) (Semiárida, 2024)
The use of grass seeds is a strategy for grassland recovery in different regions. The objective of this study was to describe traits of seeds and seedlings of interest, and their respective variability in populations of Piptochaetium napostaense, a forage species from the Espinal grasslands. The seed weight, germination attributes and vigor of seedlings were studied in 7 populations of Piptochaetium napostaense collected in the Espinal region, delimited to the north by the locality of Victorica, and to the south by the locality of Perú, in the province of La Pampa. Differences were presented between populations for the variables seed weight and germination. Population 3 showed the highest values in weight (670 mg per 100 seeds), and P6 showed the highest percentage of germination (62 %). The vigor of seedlings was a variable that did not present differences between populations. The weight of seeds was positively correlated with the aerial height of seedlings. The improvement of this species by selection of characters would be feasible in attributes such as germination and weight, being a useful strategy in the rehabilitation of grasslands, with the purpose of increasing the frequency of forage species.